REPERFUSION MYOCARDIAL INJURY AFTER PRIMARY PERCUTANEOUS CORONARY INTERVENTION IN PATIENT WITH ACUTE ST-ELEVATION MYOCARDIAL INFARCTION. CLINICAL OBSERVATION - N. A. Kosheleva; N. A. Magdeeva; V. V. Phrontaseva; O. S. Lobanova; Z. B. Hashucaeva (Архивъ внутренней медицины, 2016)
The goal is to determine the possibilities of treatment of reperfusion myocardial injury in patient with acute ST-elevation myocardial infarction after percutaneous coronary intervention. Methods. Clinical observation. Results and discussion. After percutaneous coronary intervention the return of blood flow can result in reperfusion myocardial ischemia, «no-reflow» phenomenon, which is manifested with recurrent angina, disturbances of rhythm and conduction, worsening of ECG, decrease in local and global contractility of the left ventricular myocardium. Conclusion. The addition of calcium channel blockers to standard therapy can stabilize the patients condition, relief angina.